2008
DOI: 10.1021/jo801158g
|View full text |Cite
|
Sign up to set email alerts
|

Organocatalytic Asymmetric Addition of Alcohols and Thiols to Activated Electrophiles: Efficient Dynamic Kinetic Resolution and Desymmetrization Protocols

Abstract: Bifunctional urea-based cinchona alkaloid derivatives have been shown to promote highly efficient DKR reactions of azalactones using an alcohol nucleophile. The optimum catalyst is remarkably insensitive to the steric bulk of the amino acid residue, allowing alanine-, methionine-, and phenylalanine-derived azalactones to undergo DKR with unprecedented levels of enantioselectivity using a synthetic catalyst. The first DKR of these substrates by thiols and the highly enantioselective desymmetrization of a meso-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
40
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(40 citation statements)
references
References 55 publications
0
40
0
Order By: Relevance
“…The urea catalyst was capable of mediating the DKR of both unhindered azlactones (entries 1-4) and more bulky analogues (entries 5-7) with approximately equal facility to furnish orthogonally protected amino acids with very good enantioselectivity. 75 In particular, to the best of our knowledge, this represents the most selective DKR of the unhindered azlactones 96-98 by alcoholysis with a synthetic catalyst to date.…”
Section: Dynamic Kinetic Resolution Of Azlactonesmentioning
confidence: 93%
“…The urea catalyst was capable of mediating the DKR of both unhindered azlactones (entries 1-4) and more bulky analogues (entries 5-7) with approximately equal facility to furnish orthogonally protected amino acids with very good enantioselectivity. 75 In particular, to the best of our knowledge, this represents the most selective DKR of the unhindered azlactones 96-98 by alcoholysis with a synthetic catalyst to date.…”
Section: Dynamic Kinetic Resolution Of Azlactonesmentioning
confidence: 93%
“…51 After optimisation of the reaction conditions developed by Connon et al, 52 they achieved the desymmetrisation of anhydride 57 in 80% ee with ten equivalents of methanol and 2 mol% of catalyst C-12 (Scheme 20a). 51 After optimisation of the reaction conditions developed by Connon et al, 52 they achieved the desymmetrisation of anhydride 57 in 80% ee with ten equivalents of methanol and 2 mol% of catalyst C-12 (Scheme 20a).…”
Section: Anhydride Desymmetrisation In Synthesismentioning
confidence: 99%
“…We proposed that catalysts capable of also activating the anhydride moiety via hydrogen bonding should offer potential advantages in terms of both rate and selectivity. 69 Screening studies allowed the identification of conditions under which 1 mol% of catalyst 18 promoted the desymmetrisation of 112 (for example) at ambient temperature to give hemiester 113 in excellent yield and enantiomeric excess in 30 h (Scheme 25). We also found that allyl alcohol could be used as the nucleophile in these reactions -this allows the synthesis of both antipodes of 113 using a single catalyst system via the manipulation of allyl hemiester 114 without chromatography (113 is isolated pure after a simple acid/base wash/extraction sequence).…”
Section: Desymmetrisation Of Meso Anhydridesmentioning
confidence: 99%